High-resolution genome-wide functional dissection of transcriptional regulatory regions and nucleotides in human - Xinchen Wang (Nature Portfolio, 2018)
Millions of enhancers are predicted, but their validation remains challenging. Here, the authors report genome-wide enhancer function quantification and high-resolution dissection for millions of accessible DNA fragments, revealing driver nucleotides and helping interpret non-coding disease variants.